2018
DOI: 10.1017/s0008423917001020
|View full text |Cite
|
Sign up to set email alerts
|

Neoliberalism, Authoritarian-Populism, and the “Photo-Op Democracy” of the Publicity State: Changes to Legislative and Parliamentary Norms by the Harper Government

Abstract: Several recent reports seek to evaluate the impact of former Prime Minister Stephen Harper on Canadian democracy by documenting his government's efforts to curtail established democratic processes and mechanisms for public debate. However, this article uses examples of the Harper government's changes to legislative and parliamentary norms to demonstrate that this government's efforts to curtail multi-directional public debate were importantly accompanied by efforts to amplify unidirectional communication of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…This is also known as a joint package that includes one or a combination of various subjects incorporated into a document approved through a parliamentary vote (Goertz, 2011). The concept is regarded as a draft law with several major and minor substantive matters compiled and combined into a single large bill (Brabazon & Kozolanka, 2018). Massicotte as quoted by Hanson further reported that its practice has two advantages.…”
Section: Legal Political Context Of the Omnibus Law Used In The Law O...mentioning
confidence: 99%
“…This is also known as a joint package that includes one or a combination of various subjects incorporated into a document approved through a parliamentary vote (Goertz, 2011). The concept is regarded as a draft law with several major and minor substantive matters compiled and combined into a single large bill (Brabazon & Kozolanka, 2018). Massicotte as quoted by Hanson further reported that its practice has two advantages.…”
Section: Legal Political Context Of the Omnibus Law Used In The Law O...mentioning
confidence: 99%